KETERANGAN TERDAKWA SEBAGAI ALAT BUKTI OLEH HAKIM DALAM PERKARA KEALPAAN YANG MENGAKIBATKAN MATINYA ORANG LAIN DIJALAN RAYA - Irhammudin (Legalita, 2020)
This Research Is A Descriptive Type Of Empirical Legal Research. The Research Location Is The Kotabumi District Court. The Data Of This Study Include Primary Data And Secondary Data. Primary Data Is The Main Data In This Study. While Secondary Data Is Used To Support Primary Data. Data Collection Techniques Used Are Through Interviews And Library Research In The Form Of Books, Laws And Regulations, Archives, Documents And Others. The Data Analysis Used Qualitative Data Analysis With An Interactive Model. That The Role Of The Defendant's Statement As Evidence By The Kotabumi District Court Judge In Examining And Deciding Cases Of Negligence That Resulted In The Death Of Another Person On The Highway Is That The Defendant's Statement Is Only One Of The Legal Evidence In The Trial And Must Be Supported By Other Evidence With A Minimum Rule Of 2 Pieces Of Evidence, That The Evidence For The Defendant's Statement Is Not Evidence That Has A Binding And Decisive Nature, But Must Be Supported By Other Evidence. The Defendant's Statement Alone Is Not Sufficient To Prove His Guilt Even Though He Has Admitted His Actions, The Defendant's Statement Has Independent Evidentiary Power, Namely That The Judge Can Accept Or Remove It As Evidence By Stating The Reasons.